TRANSISI MOTIVASI BELAJAR SISWA KALA DAN PASCA PANDEMI COVID-19 - Sembiring, Desy Anita Karolina; Raja, Nova Riama Lumban; Rosiyanti, Rosiyanti; Toam, Agnes (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze student learning motivation during and after the Covid-19 pandemic, particularly during the transition from hybrid to face-to-face learning. This quantitative research employs a simple descriptive design and involves a population of tenth-grade students at SMA Negeri 1 Sentani, totaling 266 students. A sample of 156 students was determined through simple random sampling techniques. Data were collected using an online questionnaire distributed via Google Forms and measured with a five-point likert scale. Data processing involved categorizing student learning motivation scores as high, medium, and low, based on predetermined percentages. Data analysis was conducted using descriptive statistics to examine relationships between variables. The results indicate that student motivation significantly declined during the hybrid learning period, marked by restricted physical interaction and technological limitations. However, with the transition back to face-to-face learning, there was a significant increase in student motivation, driven by improved social interaction and direct support from educators. This research confirms that social interaction and emotional support play crucial roles in enhancing learning motivation. These findings underscore the importance of considering humanistic aspects in education, especially in designing post-pandemic learning strategies aimed at improving the academic success and emotional well-being of students.